Development of an environmental health profile: Kuisebmond, Walvis Bay, Namibia (June 1996) - Shroyer, Margaretha Elizabeth (Department of Environmental and Geographical Science, 2025)
A four-step methodology was used as a research structure to investigate environmental health in Kuisebmond, a traditional black township in Walvis Bay. On completion of the Urban Environmental Profile (UEP) for Walvis Bay, to address issues in the exosystem, it was found that infrastructure services provided to Kuisebmond are of a high quality. An acceptable quality and quantity of water, electricity, sewage systems and waste removal services are supplied to residents by the Walvis Bay Municipality. The road and communication infrastructure is also acceptable and schools, health care facilities and recreational areas are available. These services appear satisfactory, however a few problems were identified: Infrastructure that was previously considered adequate in Walvis Bay has to be improved to cater for the expected population growth and to cope with current demand; Kuisebmond has a very high residential density, resulting in crowding and the increase of informal settlements. Social problems include poverty, unemployment, tuberculosis, AIDS, crime and alcoholism; Environmental hazards such as water and odour pollution are not adequately addressed and waste and litter creates breeding sites for vectors of disease. To address factors in the micro- and mesosystems, an Environmental Health Survey for Poor Communities (EHSPC) was developed and applied to Kuisebmond. On completion of the EHSPC it was found that data was lacking with regard to: family health and hygiene behaviour (of major importance as the highest quality of services provided can be contaminated through unhygienic practices and behaviour); food safety and security; the level of health education; mental health, and occupational health and safety practices, especially in informal trading areas and multipurpose homes. Information regarding residential satisfaction, how people feel about their dwellings, available services, public facilities and their neighbourhood was not available. These factors, relating to quality of life (in accordance with the WHO definition where health is defined as a state of complete physical, mental and social well-being and not merely the absence of disease) are often overlooked in poor communities. An increased level of environmental health enjoyed by poor communities can contribute to the world strategy ''Health for All by the Year 2000". To achieve this objective environmental health has to include more than just infrastructure, pollution control and exposure standards. Tue human component, the factor that determines how the infrastructure is used, has to be included to provide data from a holistic perspective. This dissertation addressed issues concerning environmental health, which are not normally considered, such as house design, family health and hygiene behaviour, family safety, multipurpose homes and quality of life. Tue unit of evaluation was the human-environment interaction, in accordance with the ecosystemic perspective.